Somebody's business [large type] - Brown, Irene Bennett (Brown, Irene Bennett. Nickel Hill series, 2023)
"Jocelyn Pladson buys the livery stable in Skiddy to aid the widow of the previous owner. Citified newcomers with shady pasts and newly invented motorcars, Maretta Rudd and J. L. Cochran intend to replace the livery with a motorcar business. Fools, who ignore too soon the need for horses and mules in transportation and farm work. Rom, the teenage boy Jocelyn took in and raised, offers a race between his mule and J.L.'s Oldsmobile. The winner? J.L., furious, hires hoodlums to demolish Jocelyn's livery. Prison for J.L. looms, and Maretta leaves town. Jocelyn plans to keep the Skiddy property, the land, for a promising future"--Back cover.